The Role of Additional K-Wires on AO Type C Distal Radius Fracture Treatment with External Fixator in Young Population - Ivan Micic; Erica Kholinne; Yucheng Sun; Jae-Man Kwak; In-Ho Jeon (Advances in Orthopedics)
Objectives. Several methods have been proposed to treat AO type C distal radius fracture. External fixator has gained popularity for its simple procedure and rapid recovery. Some surgeons suggested that additional K-wires may play a critical role in the outcome. The purpose of study is to evaluate the role of additional K wires in treating distal radial fracture with external fixator regarding its outcome. Material and Methods. From January 2006 to January 2010, 40 patients with AO type C distal radius fracture were treated with external fixator, with (EF) or without additional K wires (EFK). Radiologic outcome parameters include radial inclination, volar tilt, radial length, and the presence of radiocarpal arthritis according to Knirk and Jupiter. Clinical outcomes include New York Orthopedic Hospital (NYOH) wrist scoring scale. Results. Radiographic outcome showed significant difference in regard of articular congruency at the final follow-up with the EFK group showing the advantage in maintaining the articular incongruity. NYOH wrist scoring scale showed no significant difference between both groups at final follow-up. The amount of articular step-off was less in EFK group with significant statistical finding on the final follow up. Conclusion. Both EF and EFK technique were able to provide satisfactory result in treating AO type C distal radius fractures. We observed that EFK is superior in reducing the number of radiocarpal arthritic changes compared to EF group due to its superiority in reducing articular step-off.